2003
DOI: 10.1002/hipo.10136
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of acidic calponin during dendritic spine plasticity after pilocarpine‐induced seizures

Abstract: We have previously shown that, in HEK 293 cells, overexpression of acidic calponin, an actin-binding protein, induces remodeling of actin filaments, leading to a change in cell morphology. In addition, this protein is found in dendritic spines of adult hippocampal neurons. We hypothesized that this protein plays a role in regulating actin-based filaments during dendritic spine plasticity. To assess this hypothesis, the pilocarpine model of temporal lobe epilepsy was selected because an important reorganization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 65 publications
(90 reference statements)
2
39
0
Order By: Relevance
“…We found that seizure activity causes activation (dephosphorylation) of cofilin and an associated depolymerization of F-actin, even in the absence of major structural changes to the dendrites. While a recent study found that disruption of actin networks may alter seizure threshold (SierraParedes et al, 2006) and other studies indicate that seizures may affect actin-binding proteins (Roth et al, 2001;Ferhat et al, 2003), the present study is among the first to directly show that seizures can modulate actin polymerization, as well as cofilin activation. While it is possible that the actin depolymerization might be a direct pharmacological effect of 4-AP rather than the seizure activity, preliminary data from our and other labs suggest similar effects in other seizure models (Wong, unpublished data), and p-cofilin was decreased bilaterally in this study, despite a unilateral 4-AP injection, consistent with seizure-mediated actions.…”
Section: Discussionmentioning
confidence: 39%
“…We found that seizure activity causes activation (dephosphorylation) of cofilin and an associated depolymerization of F-actin, even in the absence of major structural changes to the dendrites. While a recent study found that disruption of actin networks may alter seizure threshold (SierraParedes et al, 2006) and other studies indicate that seizures may affect actin-binding proteins (Roth et al, 2001;Ferhat et al, 2003), the present study is among the first to directly show that seizures can modulate actin polymerization, as well as cofilin activation. While it is possible that the actin depolymerization might be a direct pharmacological effect of 4-AP rather than the seizure activity, preliminary data from our and other labs suggest similar effects in other seizure models (Wong, unpublished data), and p-cofilin was decreased bilaterally in this study, despite a unilateral 4-AP injection, consistent with seizure-mediated actions.…”
Section: Discussionmentioning
confidence: 39%
“…Recent evidence suggests that specific calcium-activated enzymes, such as calcineurin, are activated in animal models of epilepsy [86]. Furthermore, actin and actin-associated proteins are regulated by acute seizures or during chronic epileptogenesis [75,87,88]. In particular, seizures lead to acute depolymerization of filamentous actin, which could directly account for structural changes in dendrites [75].…”
Section: Mechanisms Of Dendritic Injurymentioning
confidence: 99%
“…Actin filament depolymerization by latrunculin A may also alter other NMDA receptor properties, such as protein anchoring to intracellular domains, thus altering the signaling pathways activated by both synaptic and extrasynaptic receptors. [9] Alterations in several actin-related proteins, such as acidic calponin [29] and calpain [30] have been linked to epileptic seizures in different experimental models. We have recently shown that latrunculin A microperfusion has a significant effect on components of the MAPK signaling pathways such as ERK 1/2 and pp38 [27] .…”
Section: Discussionmentioning
confidence: 99%